Aconselhamento para a redução do comportamento sedentário em adultos na atenção primária à saúde - Snége, André (2021)
Counseling to reduce sedentary behavior has been shown to be a promising strategy that should be part of health promotion actions. However, there are no studies in Latin America that evaluated the prevalence of this practice in Primary Health Care. Therefore, the aim of this study was to investigate the prevalence of counseling to reduce sedentary behavior and to analyze the associated factors in adult users of Basic Units of Health of São José dos Pinhais, Paraná. Analytical, quantitative, observational, cross-sectional study, carried out in 2019, with a representative sample of 779 adults (70% women), assisted in 15 Basic Health Units (UBS), located in the urban area of the city. Participants were interviewed face-to-face and counseling was identified among those who reported receiving some counseling to reduce sedentary behavior in the past 12 months. Sociodemographic variables were analyzed (gender, age group, marital status, skin color, education, socioeconomic level), health (nutritional status, diagnosis of chronic diseases and drug consumption), access to health services (number of visits to unit in the last year) and health risk behaviors (smoking, insufficient physical activity and excessive sedentary behavior. Data were analyzed with multivariate Poisson regression in SPSS 26.0 and the significance level was maintained at 5%. The prevalence of counseling was 12.2% (95%CI: 10.0-14.0). The sociodemographic variables are gender (“female”: PR: 1.78; 95%CI: 1.11-2.85; p=0.015) and age group (“≥ 60 years old”: PR: 1.77; 95%CI: 1.04-3.02; p=0.035) showed a positive association with counseling. The probability of receiving counseling to reduce sedentary behavior was also higher among the obese (PR: 2.72; 95%CI: 1.38-5.36; p=0.004), those who consume 1 to 3 continuous-use medications (PR: 1.91; 95%CI: 1.02-3.58; p=0.042), and those who sit for a time equal to or greater than 1.8 hours per day sitting (p<0.05). The greatest magnitude of association was found among those who sit for at least 6.2 hours a day in the sitting position (PR: 3.83; 95%CI: 2.09-7.03; p<0.001). It is concluded that one in 10 adults receive counseling to reduce sedentary behavior and the population groups with greater exposure to counseling were women, the elderly, obese, those who use one to three medications daily and those who remain prolonged time of day in sedentary behavior. This approach and results can help managers and professionals of the Basic Health Units teams to implement and direct specific counseling actions to reduce sedentary behavior among population groups more exposed to low counseling, such as men, young adults, those with normal weight, those who do not consume continuous medications and the most physically active.